Extremely-low-temperature magnetic refrigeration material with pyrochlore structure and preparation method and application of extremely-low-temperature magnetic refrigeration material

By adopting the quantum-resistance magnetic material Ce2Sn2O7 with a calcinite structure, the performance and reliability problems of existing paramagnetic salt materials in extremely low temperature refrigeration are solved using its quantum spin ice state and topological order, and an efficient extremely low temperature refrigeration below 100mK is achieved.

CN119786175AActive Publication Date: 2025-04-08BEIHANG UNIV +1

Patent Information

Application Number
CN202411021866.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-04-08
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

In extremely low temperature refrigeration applications, existing paramagnetic salt materials have problems such as low magnetic ion density, unstable chemical properties, weak exchange interactions, low refrigeration efficiency and difficult processing, which limit their performance and reliability in practical applications.

Method used

The quantum-resistance magnetic material Ce2Sn2O7, which adopts the calcined stone structure, achieves high magnetic entropy density and good thermal conductivity through its unique quantum spin ice state and "hidden" topological order, thereby improving refrigeration efficiency.

Benefits of technology

It realizes efficient refrigeration at extremely low temperatures below 100mK, with the advantages of tight structure, stable chemicals, large magnetic entropy density and simple preparation, which significantly improves the performance and reliability of extremely low temperature refrigeration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786175A_ABST
    Figure CN119786175A_ABST
Patent Text Reader

Abstract

The invention provides an extremely-low-temperature magnetic refrigeration material with a pyrochlore structure, the chemical formula of the extremely-low-temperature magnetic refrigeration material is Ce2Sn2O7, the extremely-low-temperature magnetic refrigeration material belongs to a cubic system, and the space group of the extremely-low-temperature magnetic refrigeration material is Fd-3m. Compared with a traditional magnetic refrigeration material (paramagnetic salt hydrate), the novel extremely-low-temperature magnetic refrigeration material Ce2Sn2O7 of the pyrochlore structure has good magnetocaloric performance, can achieve 100 mK-level extremely-low-temperature refrigeration in the heat insulation and demagnetization actual measurement process, and meanwhile has the advantages of being compact in structure, high in stability, large in magnetic entropy density, easy to prepare and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultra-low temperature magnetic refrigeration material with a pyrochlore structure and a preparation method and application thereof. Background Art

[0002] Ultra-low temperature refrigeration technology is widely used in national security and strategic high-tech fields such as large scientific facilities, deep space exploration, materials science, and quantum computing. However, in the past, ultra-low temperature refrigeration has always been inseparable from the scarce helium element, especially the global helium shortage problem. Scientists have found that adiabatic demagnetization refrigeration does not require helium resources, which makes this cooling technology increasingly important in various applications.

[0003] The magnetocaloric effect refers to the law and phenomenon of controlling the temperature change of magnetic materials by applying an external magnetic field under adiabatic conditions. When the external magnetic field increases, the spin disorder of the magnetic material decreases, resulting in a decrease in magnetic entropy and a corresponding increase in lattice entropy, which ultimately manifests as an increase in the material temperature; conversely, when the magnetic field weakens, the temperature of the magnetic material decreases, thereby achieving a cooling effect.

[0004] By utilizing the magnetocaloric effect, designing the Carnot cycle through isothermal magnetization and adiabatic demagnetization, the adiabatic demagnetization refrigeration technology developed can achieve the purpose of refrigeration. This technology is not affected by the gravity environment, does not rely on helium resources, has the advantages of high refrigeration efficiency, low vibration and high reliability, and is widely used in deep space exploration and other fields.

[0005] In adiabatic demagnetization refrigeration technology, the commonly used magnetic materials are paramagnetic salts, such as ammonium ferric sulfate (FeNH4(SO4)2·12H2O, FAA), potassium chromium sulfate (KCr(SO4)2·12H2O, CPA) and cerium magnesium nitrate (Ce2Mg3(NO3) 12 ·24H2O, CMN) etc. The characteristic of these paramagnetic salt materials is that there is almost no interaction between their magnetic ions, so that magnetic order will only appear at very low temperatures. This characteristic enables paramagnetic salt materials to retain entropy in a very low temperature range, so they have a good ultra-low temperature refrigeration effect.

[0006] In 1933, physicist Giauque experimentally used the hydrated paramagnetic salt material Gd2(SO4)3·8H2O as a refrigerant for the first time, achieving an extremely low temperature of 250mK, for which he won the Nobel Prize.

[0007] However, after in-depth literature research and a large number of experimental explorations, the inventors of the present invention found that there are many limitations in the use of existing paramagnetic salts as refrigerants in practical applications. First, traditional paramagnetic salts are mostly hydrates, and their magnetic ion density is relatively low, which directly limits the improvement of refrigeration power per unit volume. At the same time, its chemical properties are quite unstable and susceptible to deliquescence and decomposition, which undoubtedly increases the difficulty and complexity in practical applications. Secondly, the exchange interaction inside the paramagnetic salt is weak, making it difficult to effectively utilize the magnetically excited thermal conductivity, and it can only rely on the lattice heat conduction mechanism, resulting in low refrigeration cold extraction efficiency. Finally, the growth cycle of hydrated paramagnetic salts is long, the processing process is difficult, and it is often accompanied by a certain degree of corrosiveness. The above-mentioned unfavorable factors have greatly restricted it in practical applications.

[0008] On this basis, the inventor's research team proposed for the first time that the emerging quantum frustrated magnetic materials are expected to solve the above problems to a certain extent. This material not only has the characteristics of compact structure and high chemical stability, but also has a large spin density, which provides the possibility of improving refrigeration efficiency. More importantly, the quantum frustration effect allows the material to maintain spin fluctuations even at extremely low temperatures, thereby ensuring significant magnetic entropy. In addition, due to the large exchange interaction inside it and the large number of low-energy magnetic excitations gathered near the quantum phase transition point, these characteristics together give the quantum frustrated magnetic material excellent thermal conductivity. Therefore, this emerging material is expected to solve the limitations of traditional paramagnetic salts in practical applications to a certain extent, and open up new avenues for the development of refrigeration technology. Summary of the invention

[0009] Therefore, the purpose of the present invention is to provide a quantum frustrated magnetic material with compact structure, stable chemical properties, high spin density, simple preparation conditions and the ability to achieve extremely low temperatures below 100mK, as an excellent working medium for adiabatic demagnetization refrigeration.

[0010] During the research and development process, the inventors of the present invention discovered that the "two-in, two-out" rule of the tetrahedral dipole moment gives the rare earth pyrochlore material a unique quantum spin ice state; however, the higher multi-level degrees of freedom possessed by f electrons often lead to the formation of "hidden" topological order. Taking Ce2Sn2O7 as an example, its ground state is proposed to be a magnetic octupole quantum spin liquid; the results of related neutron scattering experiments show that compared with magnetic dipoles, Ce2Sn2O7 exhibits a more complex magnetization density distribution. Therefore, the inventors of the present invention realized that the continuous excitation of its spin and the potential "hidden" topological order will produce a significant magnetocaloric effect, making it likely to become an excellent magnetic refrigeration material.

[0011] In the present invention, the term "extremely low temperature" generally refers to a temperature not higher than 1K.

[0012] The first aspect of the present invention provides a pyrochlore structured ultra-low temperature magnetic refrigeration material, the chemical formula of which is Ce2Sn2O7, belonging to the cubic crystal system, and the space group is Fd-3m.

[0013] According to the ultra-low temperature magnetic refrigeration material provided by the present invention, the lattice constant of the material is

[0014]

[0015] Figure 1 Schematic diagram of the crystal structure of pyrochlore Ce2Sn2O7 provided by the present invention. Specifically, Figure 1 The image above shows the positions of all atoms in the Ce2Sn2O7 lattice, where the green atom with the largest diameter represents the magnetic ion Ce. 3+ ; For simplicity, Figure 1 The figure below shows only the 3+ and O 2+ The tetrahedral structure is formed. Figure 1 It can be seen that the magnetic ion Ce 3+ The spin pointing satisfies the "two in, two out" rule.

[0016] According to the ultra-low temperature magnetic refrigeration material provided by the present invention, the Curie-Weiss temperature of the ultra-low temperature magnetic refrigeration material is -0.124K.

[0017] According to the ultra-low temperature magnetic refrigeration material provided by the present invention, the magnetization intensity of the ultra-low temperature magnetic refrigeration material increases with the increase of the external magnetic field intensity. At a temperature of 1.8K, at a temperature of 1.8K, the magnetization of the ultra-low temperature magnetic refrigeration material reaches saturation at a magnetic field intensity of about 7T.

[0018] According to the ultra-low temperature magnetic refrigeration material provided by the present invention, at a temperature of 2.4K, the maximum magnetic entropy change of the ultra-low temperature magnetic refrigeration material under a 0-7T magnetic field change is ≤4.677J / kg·K -1 .

[0019] According to the ultra-low temperature magnetic refrigeration material provided by the present invention, when demagnetization is performed from an 8T magnetic field at an ambient temperature of 1.8K and the magnetic field drops to zero, the temperature of the ultra-low temperature magnetic refrigeration material reaches 91.3mK;

[0020] At an ambient temperature of 1.8K, when demagnetization is performed from a 6T magnetic field and the magnetic field drops to zero, the temperature of the ultra-low temperature magnetic refrigeration material can reach 106mK.

[0021] The second aspect of the present invention provides a method for preparing the ultra-low temperature magnetic refrigeration material with the pyrochlore structure, the preparation method comprising:

[0022] (1) The raw materials CeO2, SnO2 and Sn are mixed in a molar ratio of 4:3:1 and fully ground;

[0023] (2) The ground raw materials are pressed into tablets and vacuum-sealed in a quartz tube to synthesize pyrochlore-structured Ce2Sn2O7 using a solid-phase reaction method.

[0024] According to the preparation method provided by the present invention, the solid phase reaction method comprises: reacting the reaction raw materials at 920-980° C. for 10-48 hours, taking them out and grinding them sufficiently, and then sintering them at 950-1050° C. for 10-48 hours.

[0025] In some preferred embodiments of the present invention, the solid phase reaction method comprises: reacting the reaction raw materials at 940-960° C. for 30-40 hours, taking them out and grinding them sufficiently, and then sintering them at 980-1020° C. for 10-48 hours.

[0026] The third aspect of the present invention provides the use of the ultra-low temperature magnetic refrigeration material described in the first aspect of the present invention or the ultra-low temperature magnetic refrigeration material prepared according to the preparation method of the second aspect of the present invention as an adiabatic demagnetization refrigeration medium.

[0027] The new pyrochlore-structured ultra-low temperature magnetic refrigeration material Ce2Sn2O7 provided by the present invention has good magnetocaloric properties compared to traditional magnetic refrigeration materials (paramagnetic salt hydrates), and can achieve ultra-low temperature refrigeration of 100mK level during adiabatic demagnetization measurement. It also has the advantages of compact structure, high stability, high magnetic entropy density and easy preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:

[0029] Figure 1 Schematic diagram of the crystal structure of Ce2Sn2O7 with pyrochlore structure of the present invention;

[0030] Figure 2 It is a comparison chart of the X-ray diffraction spectrum of the Ce2Sn2O7 material prepared in Example 1 of the present invention and the standard card;

[0031] Figure 3 The magnetic susceptibility temperature curve and the magnetic susceptibility inverse curve of the Ce2Sn2O7 material obtained in Example 1;

[0032] Figure 4 The isothermal magnetization curves of the Ce2Sn2O7 material prepared in Example 1 at different temperatures of 1.8 to 10 K;

[0033] Figure 5 The isothermal magnetic entropy change curve of the Ce2Sn2O7 material prepared in Example 1 during the isothermal magnetization process as a function of the magnetic field;

[0034] Figure 6 The temperature change curves of the Ce2Sn2O7 material of the present invention when demagnetization is started from the initial magnetic fields of 2T, 4T, 6T and 8T respectively at an ambient temperature of 1.8K; and the temperature change curve of the spin ice material Er2Ti2O7 as a control after demagnetization at an initial magnetic field of 4T at 2K;

[0035] Figure 7 The temperature of the Ce2Sn2O7 material of the present invention changes with time during the field reduction process and after the magnetic field drops to zero. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.

[0037] Example 1

[0038] Preparation of pyrochlore structure Ce2Sn2O7

[0039] (1) CeO2, SnO2, and Sn (all with a purity of 99.99%) are used as raw materials, and the raw materials are prepared according to a stoichiometric molar ratio of 4:3:1, and the raw materials are mixed evenly and fully ground;

[0040] (2) The tablets were pressed using a tablet press to make the reaction more complete, and then vacuum sealed in a quartz tube (to prevent Sn from reacting with O2 in the air). The tablets were reacted at 950°C for 35 hours, taken out and fully ground, and then sintered at 1000°C for 35 hours. The solid phase reaction method was used to synthesize the pure phase powder.

[0041] Figure 2 This is a comparison chart between the X-ray diffraction spectrum of the Ce2Sn2O7 material prepared in this embodiment and the standard card.

[0042] Magnetic properties characterization

[0043] The magnetic properties of Ce2Sn2O7 material prepared in Example 1 were characterized by using Quantum Design MPMS test system. The magnetic susceptibility and magnetization intensity data are shown in Figure 3-5 shown.

[0044] Figure 3 The magnetic susceptibility temperature curve and the magnetic susceptibility inverse curve of the Ce2Sn2O7 material obtained in Example 1 are shown in FIG. Figure 3 a) shows the magnetic susceptibility temperature curve and the magnetic susceptibility reciprocal curve from 1.8 to 15 K, and the Curie-Weiss fitting curve from 1.8 to 6 K; Figure 3Figure b) shows the magnetic susceptibility temperature curve and the inverse magnetic susceptibility curve from 1.8 to 300 K, where the fluctuations in the box are caused by crystal field splitting (the inverse magnetic susceptibility tends to a constant).

[0045] Figure 3 The results show that Ce2Sn2O7 satisfies the Curie-Weiss law at very low temperatures, and the Curie-Weiss temperature is fitted to be -0.124K. 3+ The ions are affected by the crystal field, and the ground state is a double state. At very low temperatures, it shows an effective spin of -1 / 2 and has a weak antiferromagnetic interaction. As the temperature rises, the crystal field splits the first excited double state and begins to contribute to magnetism, which is manifested as Figure 3 b) Fluctuations within the box in the figure.

[0046] The magnetization intensity-magnetic field change data of the Ce2Sn2O7 material prepared in Example 1 was tested. Figure 4 The isothermal magnetization curves of the Ce2Sn2O7 material prepared in Example 1 at different temperatures of 1.8 to 10 K; Figure 5 This is the calculated curve of isothermal magnetic entropy change versus magnetic field during the isothermal magnetization process.

[0047] Figure 4 The results in show that the magnetization intensity of Ce2Sn2O7 increases monotonically with the increase of external magnetic field. At 1.8K, it is close to saturation at 7T magnetic field. Based on this and the Maxwell relationship, the entropy change in the isothermal magnetization process at different temperatures is obtained, such as Figure 5 As shown in Figure 2, at a temperature of 2.4 K, the magnetic entropy can change by 2.945 J / (mol·K) under a 7 T magnetic field. These experimental results show that pyrochlore-structured Ce2Sn2O7 materials can achieve refrigeration under magnetic field regulation.

[0048] Magnetic refrigeration performance characterization

[0049] The Ce2Sn2O7 material prepared in Example 1 was mixed with an equal mass of silver powder to enhance the thermal conductivity of the sample, and then pressed into two cylinders with a diameter of 8 mm, and a thermometer was placed therein, and an adiabatic demagnetization test was performed using a commercial Quantum Design PPMS test system.

[0050] The temperature change curves of the Ce2Sn2O7 material of the present invention when demagnetizing from the initial magnetic fields of 2T, 4T, 6T and 8T respectively at an ambient temperature of 1.8K; and the temperature change curve of the spin ice material Er2Ti2O7 as a control after demagnetization at an initial magnetic field of 4T at 2K, as shown in FIG. Figure 6 shown.

[0051] Figure 6It shows that when the magnetic field drops to zero, the temperature of the Ce2Sn2O7 material of the present invention reaches 91.3mK and 106mK when the initial magnetic field is 8T and 6T, respectively. Compared with the traditional spin ice material Er2Ti2O7, under the same conditions, when the magnetic field drops to zero, the temperature of Ce2Sn2O7 continues to drop to 75mK and 103mK, and is maintained near the lowest temperature for a long time. This comparison result shows that Ce2Sn2O7, as a material with the same pyrochlore structure, is a candidate material for quantum spin liquid. It does not show order until extremely low temperatures, has stronger quantum fluctuations, and has a large number of degenerate states in the ground state to carry entropy. Therefore, during the adiabatic demagnetization process, very low temperatures can be reached.

[0052] Figure 7 The figure shows the temperature change curve of the Ce2Sn2O7 material of the present invention over time during the field reduction process and after the magnetic field is reduced to zero. The inset is an enlarged view of the temperature change of the sample after the magnetic field is returned to zero. It can be seen that the Ce2Sn2O7 material of the present invention is still cooling down after the magnetic field is reduced to 0, and maintains near the lowest temperature for a long time.

[0053] From the above performance characterization, it can be seen that the pyrochlore structured Ce2Sn2O7 material has good magnetocaloric properties and can achieve ultra-low temperature refrigeration of 100mK during the adiabatic demagnetization measurement process. It also has the advantages of compact structure, high stability, high magnetic entropy density and simple preparation.

[0054] The above embodiments are preferred implementation modes of the present invention, but the present invention is not limited to the above embodiments. Any other modifications, equivalent substitutions and improvements made without departing from the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A pyrochlore structured ultra-low temperature magnetic refrigeration material, the chemical formula of which is Ce2Sn2O7, belonging to the cubic system, and the space group is Fd-3m.

2. The ultra-low temperature magnetic refrigeration material according to claim 1, wherein: The lattice constant of the material is 3. The ultra-low temperature magnetic refrigeration material according to claim 1 or 2, wherein: The Curie-Weiss temperature of ultra-low temperature magnetic refrigeration materials is -0.124K.

4. The ultra-low temperature magnetic refrigeration material according to any one of claims 1 to 3, wherein: The magnetization intensity of the ultra-low temperature magnetic refrigeration material increases with the increase of the external magnetic field intensity; at a temperature of 1.8K, the magnetization of the ultra-low temperature magnetic refrigeration material reaches saturation at a magnetic field intensity of 7T.

5. The ultra-low temperature magnetic refrigeration material according to any one of claims 1 to 4, wherein: At 2.4K, the maximum magnetic entropy change of the ultra-low temperature magnetic refrigeration material under 0-7T magnetic field change is ≤4.677J / kg·K -1 .

6. The ultra-low temperature magnetic refrigeration material according to any one of claims 1 to 5, wherein: At an ambient temperature of 1.8K, when demagnetization is performed from an 8T magnetic field and the magnetic field drops to zero, the temperature of the ultra-low temperature magnetic refrigeration material reaches 91.3mK; At an ambient temperature of 1.8K, demagnetization is performed from a 6T magnetic field. When the magnetic field drops to zero, the temperature of the ultra-low temperature magnetic refrigeration material reaches 106mK.

7. The method for preparing the ultra-low temperature magnetic refrigeration material according to any one of claims 1 to 6, the method comprising: (1) The raw materials CeO2, SnO2 and Sn are mixed in a molar ratio of 4:3:1 and fully ground; (2) The ground raw material is pressed into tablets and vacuum-sealed in a quartz tube using a solid phase reaction method. Synthesis of pyrochlore-structured Ce2Sn2O7.

8. The preparation method according to claim 7, wherein: The solid phase reaction method comprises: reacting the reaction raw materials at 920-980° C. for 10-48 hours, taking them out and grinding them sufficiently, and then sintering them at 950-1050° C. for 10-48 hours.

9. The preparation method according to claim 8, wherein: The solid phase reaction method comprises: reacting the reaction raw materials at 940-960° C. for 30-40 hours, taking them out and grinding them sufficiently, and then sintering them at 980-1020° C. for 10-48 hours.

10. Use of the ultra-low temperature magnetic refrigeration material according to any one of claims 1 to 6 or the ultra-low temperature magnetic refrigeration material prepared by the preparation method according to any one of claims 7 to 9 as an adiabatic demagnetization refrigeration medium.

Citation Information

Patent Citations

  • Pyroelectric material and preparation method thereof

    CN103601489A

  • Method of treating powder made from cerium oxide using an ion beam

    CN105431229A

  • Design method of cascade type liquid-helium-free refrigerator based on novel anti-contusion magnetic material

    CN114383338A

  • Application of triangular lattice material Ba3Yb (BO3) 3 as extremely low temperature magnetic refrigeration working medium

    CN117476303A

  • Cooling device and cooling method based on magnetoelectric coupling

    DE102018118813B3

Cited By

  • Magnetic refrigeration module based on spark plasma sintering and preparation method and application thereof

    CN121061145A

  • Europium-based aluminosilicate extremely-low-temperature magnetic refrigeration material as well as preparation method and application thereof

    CN122233392A